`Sclerosing haemangioma' of the lung: an alternative view of its development. Issue 10 (October 1973) - Kennedy, A.
Abstract : `Sclerosing haemangioma' is a name which has been applied to a group of uncommon benign pulmonary lesions characterized by their papillary nature, a sclerotic stroma containing lipid, and, in some cases, evidence of haemorrhage. There is little evidence that these lesions are really angiomatous. Studies of two examples removed surgically after being discovered as incidental radiographic findings, show that the cells lining the papillae have large vacuoles which contain whorled, electron-dense inclusions. These epithelial cells have the features of granular pneumonocytes, cells known to contain phospholipid. Both lipid and cholesterol are abundant in the stroma of both tumours and the lipid is distributed in a nodular fashion. Histochemically the lipid gives a strong reaction to stains for phospholipid and it is suggested that the lipid is derived, not from the haemorrhage, but is produced by the epithelial element of the tumour.